Enhancing Readiness for Preeclampsia–Eclampsia among Pregnant Women and Their Husbands through Family-Based Digital Education: A Quasi-Experimental Study - Haryadi Haryadi; Fidyah Aminin; Ayi Diah Damayani; Dewi Mey Lestanti Mukodri; Aura Bella Gizta (Poltekita: Jurnal Ilmu Kesehatan, 2026)
Background: Preeclampsia–eclampsia remains a major contributor to maternal morbidity and mortality, highlighting the need for early recognition and family involvement. Family-based digital education may support preparedness by improving knowledge and behavioral responses. This study aimed to evaluate the association between a family-based digital education application (Si PaPa GaSi) and changes in knowledge, attitudes, and motivation regarding preeclampsia–eclampsia. Methods: A quasi-experimental study with a pre–post test control group design was conducted among 100 pregnant women–husband pairs (50 intervention, 50 control) at Berakit Primary Health Center in November 2024. The intervention group received standard health education plus access to the application, while the control group received health education only. Outcomes were assessed using structured questionnaires before and two weeks after the intervention. Data were analyzed using Wilcoxon signed-rank tests for within-group comparisons and Mann–Whitney U tests for between-group comparisons. Results: Within-group analysis showed significant improvements in knowledge, attitudes, and motivation in both groups (p < 0.05). However, between-group analysis revealed no significant difference in knowledge (U = 1119.5; p = 0.214; r = 0.12), while significant differences were observed in attitudes (U = 957.5; p = 0.028; r = 0.22) and motivation (U = 887.0; p = 0.005; r = 0.28), indicating small to moderate effect sizes. Conclusion: The Si PaPa GaSi application was associated with improvements in attitudes and motivation, but not additional gains in knowledge compared to standard education alone. These findings suggest that family-based digital education may enhance behavioral readiness and partner involvement in maternal health, although further research with longer follow-up and randomized designs is needed.